The Influence of Brand Image, Service Quality, and Religiosity on Customer Loyalty Through Satisfaction as a Mediating Variable at Bank Syariah Indonesia (BSI) in Banda Aceh - Ilham Maulana; Ridwan Nurdin; Hendra Halim (International Journal of Kita Kreatif, 2026)
This research focuses on the influence of Brand Image, Service Quality, and Religiosity on Customer Loyalty, mediated by customer satisfaction at Bank Syariah Indonesia (BSI) in Banda Aceh. In Aceh Province, the operation of sharia financial institutions is comprehensively regulated through Qanun Aceh Number 11 of 2018 concerning Sharia Financial Institutions (LKS), which implies that customer loyalty is determined not only by service-related aspects but also by the observance of sharia values. Using the SmartPLS 4.0 application, this research implemented the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method within a quantitative research approach. The data were gathered through a Likert scale questionnaire distributed to 150 active BSI customers in Banda Aceh who were selected using purposive sampling. Based on the findings, Brand Image and Service Quality significantly and positively affect customer satisfaction, whereas Religiosity does not significantly influence customer satisfaction. The results further indicate that customer satisfaction significantly affects Customer Loyalty. In addition, customer satisfaction mediates the influence of Brand Image and Service Quality on Customer Loyalty, but it does not serve as a mediator between Religiosity and Customer Loyalty. These findings indicate that the loyalty of BSI customers in Banda Aceh is more dominantly influenced by brand image and service quality through satisfaction, rather than Religiosity.